PARTISIPASI MASYARAKAT DALAM PROGRAM KELUARGA BERENCANA DI KECAMATAN PEDURUNGAN - Niken Septihandini Puspaningtyas; Hardi Warsono; Aufarul Marom (Journal of Public Policy and Management Review, 2014)
Public participation is an important aspect in the success of the government's development program. Family planning is one government program that aims to control the number of residents with a way to control birth spacing and limiting births. Another goal of family planning is to improve the quality of future generations. In the family planning programs in Sub-district Pedurungan, public participation is a form of public awareness to share the support of one of the national government's programs in an effort to control the population and improving the quality of human resources. Technical Implementation Unit of Bapermasper and KB (UPTB) Sub-district Pedurungan which is representative of bapermasper and KB Semarang acts as a supervisor, executive and government officials who deal with matters of family planning in Sub Pedurungan. The purpose of this research is to see the form of community participation in family planning programs, the level of community participation in family planning programs and the factors that influence community participation in planning programs in Sub-district Pedurungan. The results of this research are the form of community participation in family planning programs in Sub Pedurungan is pseudo participation. Levels of community participation is at the level of tokenism and there are three factors that affect the participation of the six factors studied . Factors affecting the society is education background , gender and external factors comes from the government